Resiliência e conforto térmico em habitações de interesse social horizontais em Uberlândia (MG): avaliação para orientação de reformas - Bortoli, Karen Carrer Ruman de (2023)
Accelerated urban transformations have primarily exposed the most vulnerable to the negative effects of climate and its changes. Simultaneously, Social Housing (SH), provided through the Minha Casa, Minha Vida (PMCMV) program in Brazil, has led to situations of thermal stress and unhealthiness due to their climatic inadequacy. This, coupled with plot densification resulting from self-built renovations without considering potential negative interactions between construction features and climate, hinders access to natural ventilation and solar radiation in dwellings. The outcome is thermal discomfort, increased energy demand, and health problems related to the habitual experience of extreme temperatures, all of which compromise the resilience of SH to climate. The thesis starts from the hypothesis that it is possible to measure and promote resilience in in-use horizontal SH through Thermal Comfort by observing the indicators "Bioclimatic Building" and "Climate Sensitivity," in a case study. To this end, two developments of horizontal SH from the PMCMV located in Bioclimatic Zone 4 (Uberlândia/MG) were evaluated using Post-Occupancy Evaluation (POE) tools. The impacts and resilience in these SH were observed through questionnaires, morphological analysis, computational simulation, and a resilience ruler (evaluating indicators from "1" – for "non-resilient," to "5" – for "very resilient"). Among the impact assessment results, it stood out that, on average, 81.05% of the research subjects are bothered by heat, 43.17% perceived the ventilation as insufficient, and 78.3% reported experiencing health problems due to heat in their dwellings. Furthermore, it was found that within the expanded dwellings, thermal discomfort due to heat, according to the adaptive method, is, on average, 15.78% higher than what is observed outdoors. These results indicate the low quality of the thermal environment in self-expanded horizontal SH. In the resilience assessment, the average score achieved for the proposed indicators in the case study was 2.13 ("low resilience"). Aspects such as the specification of construction systems, interaction with landscaping, and user behaviors in terms of communication and seeking of information about the climate received scores below 2 ("non-resilient"), highlighting areas that require priority attention for improvement in the case study. Based on the diagnosis, guidance sheets for renovations were developed to enhance resilience through Thermal Comfort, supporting effective provision of technical assistance for SH in the case study and similar contexts. The work expands knowledge about the relationship between transformations in horizontal SH and resilience based on users' thermal comfort, simultaneously addressing the Sustainable Development Goal nº 11 commitment of making cities and human settlements inclusive, safe, resilient, and sustainable. It emphasizes the role of virtuous design methodologies, such as POE, in promoting resilience and inspiring best practices by public administration, designers, and residents of SH.